Peran Career Search Efficacy Terhadap Career Adaptability pada Mahasiswa - C.M. Indah Soca R. Kuntari; Indah Puspitasari; Gianti Gunawan (Humanitas (Jurnal Psikologi), 2025)
University students are required to explore various career options and develop self-awareness to identify occupations that align with their interests and personalities. This exploration process, referred to as career search efficacy (CSE), is believed to facilitate the development of career adaptability (CA) a psychosocial construct that reflects an individual's readiness and resources to cope with unpredictable career paths and role ambiguities. This study aimed to examine the role of CSE in predicting CA among undergraduate students. Using a quantitative approach, data were collected from 103 participants through standardized questionnaires and analysed using simple linear regression. The results revealed a significant positive relationship between CSE and CA, with CSE accounting for 43.6% of the variance in CA (R² = 0.436; p < 0.001). These findings provide empirical support for career construction theory and underscore the importance of strengthening career exploration self-efficacy in higher education settings. Implications for career counselling practices and future research directions are discussed.